2021
DOI: 10.3389/fpsyg.2020.600570
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Behavioral Biases on Herding Behavior of Investors in Islamic Financial Products

Abstract: The study aimed to investigate the impact of behavioral biases on herding for Islamic financial products with the mediation of shariah literacy. An adopted questionnaire from several published studies was used to collect data. The data were collected from 410 respondents and were analyzed with SmartPLS. The results for the direct impact showed that self-attribution, illusion of control, and information availability have a positive and significant impact on herding for Islamic financial products while shariah l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 61 publications
4
23
0
Order By: Relevance
“…Each investor’s strategy for making investment decisions is one of a kind since each person develops their own set of investing tenets or copies the strategies of other investors. It encourages irrational conduct regarding investment decisions and quantifies the financial literacy trade-off in the context of such a phenomenon ( Din et al, 2021 ).…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…Each investor’s strategy for making investment decisions is one of a kind since each person develops their own set of investing tenets or copies the strategies of other investors. It encourages irrational conduct regarding investment decisions and quantifies the financial literacy trade-off in the context of such a phenomenon ( Din et al, 2021 ).…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…Besides, it has been proven that the teachers are exhausted and stressed out when they have to teach children with disorders such as motor skills, social behavior issues, and intellectually disabled children as compared to the regular children due to the challenges faced ( Jovanović et al, 2019 ). Another study reported that the increasing levels of teacher burnout in special schools is linked to the challenging behaviors exhibited by the special children ( Sun et al, 2019 ; Din et al, 2021 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, it has no sample size restriction, is effective for statistical model building along with forecasting, is precise and accurate in estimation, has soft modelling assumptions, does not require normality of data, and is suitable, especially in the case of mediation (Iacobucci et al, 2007;Osborne, 2011;Hair et al, 2014Hair et al, , 2017Ramli and Nartea, 2016). Moreover, SEM combines two powerful statistical approaches, exploratory factor analysis and structural path analysis, which enable the simultaneous assessment of the measurement model and the structural model (Hair et al, 2017;Din et al, 2021).…”
Section: Methodsmentioning
confidence: 99%
“…The banking sector contributes significantly to the economy (Din et al, 2020). Din et al (2021) reported few studies thatexamined the economic impact of the Islamic financial sector. The model of Islamic banking is governed under Shari'ah law, and its fundamental principles are based on "fairness" and "interest-free" (Suleiman, 2001).…”
Section: Introductionmentioning
confidence: 99%